Perspectives for Cyber Strategists on Law for Cyberwar - Charles J. Dunlap Jr. (My University, 2016)
Document offers some broad legal considerations to facilitate thinking about the role of Laws Of Armed Conflict (LOAC)  in cyberwar and suggests cautions for the military cyber strategist in the future.